ANALYSIS OF FLOUTING MAXIM FOUND IN THE YOON PICTURE BOOK SERIES BY HELEN RECORVITS - Alifah Sekar Algoddri; Gurendi Wiwoho (Universitas 17 Agustus 1945 Semarang, 2022)
The purpose of this research is to find out the types in Yoon’s picture books series, and to analyze their implied meanings. The method used in this study is qualitative descriptive. The data used in this study are three series of picture books by Helen Recorvits, that is My Name is Yoon, Yoon and the Jade Bracelet, and Yoon and the Christmas Mitten. The data used in this study are utterances containing flouting maxims in the three series picture books by Helen Recorvits and to analyze the flouting maxim the researcher uses the theory of Paul Grice. The results of this study can be summarized as follow. Firstly, the types of flouting maxims found in the Yoon picture books series are flouting maxim of quality, quantity, relevance, and manner. Among the four flouting maxims, relevance flouting occurs most frequently, which means that the cases of irrelevance in the conversations show indirectly massages and irrelevantly rather than directly and relevantly. Finally, the meanings implied in the flouting maxims in the data analyze include the functions of flouting maxims to refuse, to adapt, to express a feeling of envy, to avoid disappointing, to educate, and to respect other. Keywords: flouting maxim, implied meaning, cooperative participle, picture books, pragmatics.